Organizational stress in the context of job loss threat: The gender perspective - Smirnova, Anna Yu. (Известия Саратовского университета. Новая серия: Акмеология образования. Психология развития)
The relevance of studying stressors in organizational contexts is due to the changes in organizations and the transformation of women’s roles in modern society. The objective of the study is to analyze the stressors that affect modern employees, taking into account gender diff erences in stressor perception and existing threats. Hypothesis: the stressors of the organizational environment are specifi c for male and female employees, and the determinants of professional burnout diff er between men and women. Participants: employees of Saratov enterprises aged 18–35, with 277 males and 119 females (M = 27.3, SD = 5.8) participated in the study. Methods (tools): to diagnose current stressors, we used the technique of work stress diagnosing (by A. B. Leonova and S. B. Velichkovskaya); to determine professional burnout levels, we used the MBI C. Maslach, S. E. Jackson methodology (the Russian version N. E. Vodopyanova, E. S. Starchenkova); to identify threats of job loss we used the socio-psychological questionnaire (A. Yu. Smirnova). The results show signifi cant diff erences in how men and women respond to work-related stressors. Women were ess sensitive to certain stressors, such as overtime work, unfair pay or distribution of fi nancial incentives, and the struggle for promotion. By means of the factor analysis the analyzed stressors were grouped into two main factors: ‘fairness of organizational procedures and communication’, and ‘time and responsibility pressure’. No signifi cant diff erences have been found in the impact of the ‘time and responsibility pressure’ factor, but the ‘fairness of organizational procedures and communication’ factor was more prominent in the male group. The main conclusions. Overall, the study has found that organizational environment stressors diff er for men and women. Women are less sensitive to the eff ect of the ‘fairness of organizational procedures and communication’ factor, tend to perceive organizational procedures and communication as more satisfactory and fair, and demonstrate greater adaptability to these characteristics compared to men. Practical Significance. The data obtained can be used in the development of training programs for managing stress.